Lunar winter - Richards, William (My University, 2008)
This is the title track for a self-produced electronica album I did in 2008 [Lunar winter]. I call my style of electronica "eclectronica." Soul Dog is my electronica name (visit my site: souldogmusic.com). This track and others of my self-produced electronica/eclectronica were published (CD) as part of the MacEwan produced POP CITY 4 (2009).
Keywords: electronica; eclectronica; soul dog